Advancing energy efficiency through green bond policy: Multifamily green mortgage backed securities issuance. (15th April 2022) - Devine, Avis; McCollum, Meagan
Abstract: Diffusion of new technology, such as green bond policies, is impacted by inefficiencies and frictions as the market navigates adoption. Using data from Fannie Mae multifamily green mortgage backed security issuances, we identify possible disconnects between pricing and benefits, as well as adoption trends. Evidence indicates that loans on properties backed by green bonds that incentivize energy efficiency in multifamily buildings receive lower interest rates, lower debt service coverage ratios, and higher leverage ratios than their "brown" counterparts. Some of these findings represent stated program benefits, yet others do not. Additionally, some benefits are observed accruing to properties which are not participating in a green MBS program, despite already qualifying for participation. Supporting evidence points to drivers of adoption and program refinements which could aid in policy maximization. Our results carry implications for both existing green bond programs as well as the diffusion of green bond policy into the broader capital markets. Highlights: Studies multifamily mortgage backed securities issued under a green bond policy. Identifies disconnects in program pricing & benefits, common with new tech adoption. Green bond loans have lower interest rates & debt service coverage ratios. Green bond loans have higher loan to values, which is not a stated program benefit.